Sosialisasi Strategi Produksi Pada Usaha Dagang Kue Pia Mr Jalan Dempo VI Kelurahan Sawah Lebar Rt 21 Bengkulu - Irwanto, Tito; Pratama, Meylan; Rasuma, Hafiz Agung; Rajaliu, Haqil; Abi, Yudi Irawan (Jurnal Dehasen Mengabdi, 2022)
This community service program was carried out on Jalan Dempo VI, Sawah Lebar Village, RT 21 Bengkulu, which is one of the villages located in the Ratu Agung sub-district. The process of making this journal is aimed at how the production management functions in the manufacture and sale of cakes in the PIA "MR" business. There are various processes involved in making cakes. The process in making PIA "MR" cake has input-process-output stages, the first stage is Input, this process requires raw materials such as wheat, oil, eggs, sugar, peanuts, and butter. The second stage is the process, in this case the business owner must have complete equipment to make and print the dough in order to get maximum results in a form that is in great demand by consumers. The third stage is Output where in this process is the final stage of making PIA "MR" cakes or the results of each stage process that is passed by producing products with good quality so as to attract consumer views to buy the cake. According to Hanif, et al., (2019) in business there are important things that must be considered, namely a. application of bookkeeping in accordance with applicable rules that will help trading businesses to budget, calculate unit costs, set the right selling price, and can be the basis for making business decisions, b. unit cost analysis so that the set selling price is able to compete in the market, c. Break even point analysis to improve production efficiency and increase production capacity and market expansion, d. use of information technology to support operational activities and marketing activities